2019
DOI: 10.1186/s12889-019-6862-6
|View full text |Cite
|
Sign up to set email alerts
|

Do depression literacy, mental illness beliefs and stigma influence mental health help-seeking attitude? A cross-sectional study of secondary school and university students from B40 households in Malaysia

Abstract: Background Mental illness rates among young people is high, yet the frequency of help-seeking is low, especially among those from lower socioeconomic backgrounds. Understanding factors influencing help-seeking, such as mental illness beliefs, stigma and literacy among B40 individuals is important, but past studies are sparse. Hence, we aimed to examine the factors associated with mental help-seeking attitude among students from the B40 income bracket. Differences in beliefs toward mental illness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 50 publications
6
109
0
5
Order By: Relevance
“…Adolescent mothers in LMICs have reported a high degree of stigmatizing attitudes regarding adolescent sexual activity from healthcare providers, which reflects broader social and cultural forces to healthcare participation [3,14,20,29]. Self-stigma and younger age have been associated with mental help-seeking among young people [12], and perinatal adolescents with depression, have reported additional experiences of social stigma from family members, partners, and people in their social environments, as barriers to health care utilization [13]. Stigma is a fundamental cause of health inequities [10] and stigmatizing attitudes from clinic staff may lead to dissatisfaction with the health system, reduce the likelihood of help-seeking, and eventually compromise maternal and infant health outcomes [11,18,30].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent mothers in LMICs have reported a high degree of stigmatizing attitudes regarding adolescent sexual activity from healthcare providers, which reflects broader social and cultural forces to healthcare participation [3,14,20,29]. Self-stigma and younger age have been associated with mental help-seeking among young people [12], and perinatal adolescents with depression, have reported additional experiences of social stigma from family members, partners, and people in their social environments, as barriers to health care utilization [13]. Stigma is a fundamental cause of health inequities [10] and stigmatizing attitudes from clinic staff may lead to dissatisfaction with the health system, reduce the likelihood of help-seeking, and eventually compromise maternal and infant health outcomes [11,18,30].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of cognitive behavior therapy or other types of psychological therapy was associated with at least five times higher psychological distress, although the latter is likely due to the fact that employees who were aware of cognitive behavior therapy were plausibly more likely to have undergone it than not. Underutilization of services is not uncommon and has been documented both in Malaysia [ 14 ] and elsewhere [ 33 ]. Current findings also showed that a majority of the employees were not aware of resources available to them, which likely affected the utilization rate of such resources.…”
Section: Discussionmentioning
confidence: 99%
“…Current findings also showed that a majority of the employees were not aware of resources available to them, which likely affected the utilization rate of such resources. It is also possible, given the cultural context of this study, that employees may be reluctant to take up psychological therapy due to the stigma still associated with mental illness and/or usage of services targeted at alleviating it [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent mothers in LMICs have reported a high degree of stigmatizing attitudes regarding adolescent sexual activity from healthcare providers, which reflects broader social and cultural forces to healthcare participation (Baryamutuma, 2011;Mbeba et al, 2012;Kennedy et al, 2013;WHO, 2017). Self-stigma and younger age have been associated with mental help-seeking among young people (Ibrahim et al 2019), and perinatal adolescents with depression, have reported additional experiences of social stigma from family members, partners, and people in their social environments, as barriers to health care utilization (Kaye, 2008). Stigma is a fundamental cause of health inequities (Hatzenbuehler, Phalen, and Link, 2013) and stigmatizing attitudes from clinic staff may lead to dissatisfaction with the health system, reduce the likelihood of help-seeking, and eventually compromise maternal and infant health outcomes (White Ribbon Alliance, 2011; Holmes 2012; Mannava et al 2015).…”
Section: Introductionmentioning
confidence: 99%